Intrasubstance Tear of the Short Head of Biceps With Musculocutaneous and Median Nerve Compression - Salmons, Harold I. (J Am Acad Orthop Surg Glob Res Rev, 2019)
Traumatic intrasubstance ruptures of the biceps brachii are rare. Injury to its tendinous insertion or origin is most common. Isolated short head injuries are rare, and musculocutaneous nerve involvement has been reported for these injuries. We present a unique case report of a young, healthy man who sustained a symptomatic median and musculocutaneous nerve compression resulting from an intrasubstance tear of the short head of the biceps after a snow blower injury. Short belly rupture with injury-associated scar tissue compression of both the median and musculocutaneous nerves was identified in the operating room. Microsurgical decompression and tendon repair with a modified Mason-Allen configuration using 0-Vicryl suture were done. By 11 months postoperative, the patient experienced resolution of his arm pain, extension and flexion improvement from 0 to +140 to +15 to +150, elimination of the Tinel sign and of concomitant arm deformity, and improvement of elbow strength.